Французский напиток любви: [роман] / Елена Арсеньева - Арсеньева Елена Арсеньевна (Соблазны, 1998)
Экземпляры: ЦБ (20181019) / Инвентарный номер: 56583 / Цена: 40.00 / Сис.шифр: Р2 / Авт.знак: А 85 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6